Lysosomal dysfunction in diabetic cardiomyopathy - Kobayashi, Satoru; Hahn, Younghee; Silverstein, Brett; Singh, Mandeep; Fleitz, Adeline; Van, Jennifer; Chen, Hongling; Liang, Qiangrong (Frontiers in Aging, 2023)
Diabetes is a major risk factor for a variety of cardiovascular complications, while diabetic cardiomyopathy, a disease specific to the myocardium independent of vascular lesions, is an important causative factor for increased risk of heart failure and mortality in diabetic populations. Lysosomes have long been recognized as intracellular trash bags and recycling facilities. However, recent studies have revealed that lysosomes are sophisticated signaling hubs that play remarkably diverse roles in adapting cell metabolism to an ever-changing environment. Despite advances in our understanding of the physiological roles of lysosomes, the events leading to lysosomal dysfunction and how they relate to the overall pathophysiology of the diabetic heart remain unclear and are under intense investigation. In this review, we summarize recent advances regarding lysosomal injury and its roles in diabetic cardiomyopathy.